2020
DOI: 10.1371/journal.pone.0238484
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-3 regulates endosome-to-cytosol transfer via lipid peroxidation for cross presentation

Abstract: Antigen cross presentation, whereby exogenous antigens are presented by MHC class I molecules to CD8+ T cells, is essential for generating adaptive immunity to pathogens and tumor cells. Following endocytosis, it is widely understood that protein antigens must be transferred from endosomes to the cytosol where they are subject to ubiquitination and proteasome degradation prior to being translocated into the endoplasmic reticulum (ER), or possibly endosomes, via the TAP1/TAP2 complex. Revealing how antigens egr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Whether all the phenotypes reported for Gzma -/- mice ( Supplementary file 1 ) are compromised by Nnt and/or the mixed background remains unclear and would require new experiments to resolve, similar to those described herein for CHIKV arthritis. However, Nnt has been reported to affect redox regulation and activation in macrophages ( Ripoll et al, 2012 ; Salerno et al, 2019 ), with an intact Nnt gene conceivably reducing cross-presentation ( Dingjan et al, 2016 ; Nalle et al, 2020 ) and CD8 T cell responses ( Oberkampf et al, 2018 ). In addition, 6N vs. 6J background differences (as herein) have shown clear phenotypes in a wide range of settings ( Leskov et al, 2017 ; Morales-Hernandez et al, 2018 ; Rao et al, 2020 ; Salerno et al, 2019 ; Vozenilek et al, 2018 ; Williams et al, 2021 ; Wolf et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether all the phenotypes reported for Gzma -/- mice ( Supplementary file 1 ) are compromised by Nnt and/or the mixed background remains unclear and would require new experiments to resolve, similar to those described herein for CHIKV arthritis. However, Nnt has been reported to affect redox regulation and activation in macrophages ( Ripoll et al, 2012 ; Salerno et al, 2019 ), with an intact Nnt gene conceivably reducing cross-presentation ( Dingjan et al, 2016 ; Nalle et al, 2020 ) and CD8 T cell responses ( Oberkampf et al, 2018 ). In addition, 6N vs. 6J background differences (as herein) have shown clear phenotypes in a wide range of settings ( Leskov et al, 2017 ; Morales-Hernandez et al, 2018 ; Rao et al, 2020 ; Salerno et al, 2019 ; Vozenilek et al, 2018 ; Williams et al, 2021 ; Wolf et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…AQP3 in endosomes is needed for immune response development in mice. Adaptive immunity to pathogens starts with the presentation to CD8 + T-cells of a foreign antigen, which after ubiquitination and proteasome degradation must be released into the cytosol; this process requires AQP3 thought to act by enabling H 2 O 2 entry into the endosome to cause lipid peroxidation and release [539]. AQP8 in the inner mitochondrial membrane was shown to confer Hg 2+ -sensitive water permeability in liver cell mitochondria [540].…”
Section: Control Of Aqp Trafficking and Subcellular Localizationmentioning
confidence: 99%
“…Similarly, a-Tocopherol, an antioxidant which scavenges the ROS produced by the NADPH oxidase, reduces ROS-induced lipid peroxidation as well as the release of endocytosed proteins into the cytosol (47). Further evidence in support of ROS-induced membrane destabilization was provided by Nalle et al who demonstrated that aquaporin-3 (AQP3) transports hydrogen peroxide into endocytic organelles where it contributes to lipid peroxidation, membrane destabilization and protein release to the cytosol (49). It is worth mentioning, that apart from ROSdependent lipid modification, other lipid modifications on endocytic organelles, such as the accumulation of sphingosinebased lipids, have been proposed although there is no direct evidence for these modifications in the escape of endocytosed proteins into the cytosol as yet [reviewed in (50)].…”
Section: Delivering Endocytosed Proteins To the Cytosolmentioning
confidence: 99%